Comparative Study of The Number and Types of Seagrass in The Mangrove Forest Tourism Area of Budo Village and Darunu Mangrove Park Tourism Village, Wori District, North Minahasa Regency - Dannie R.S. Oroh; Easter Ch. M. Tulung; Margresye D. Rompas; Meiske M. Sangian (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Indonesia is the largest archipelagic country in the world consisting of 16,344 large and small islands with a coastline length of 81,000 km which is rich in biodiversity and has a very distinctive marine ecosystem such as coral reefs, mangrove forests and seagrass beds. Seagrass ecosystems in Indonesia are usually located between mangrove ecosystems and coral reefs, or near sandy beaches and coastal forests. The aim of research is finding out the comparison of the number and types of seagrass found between Budo village and Darunu village, Wori District, North Minahasa Regency. The data collection method starting with determining the location, it is carried out by conducting a direct survey using transects to determine the condition or existence of seagrass beds. A quadratic transect consists of a quadrant-shaped frame. Data collection of one transect per location, namely one transek in Budo village and one transek in Darunu village. From the results of the research in two research locations in Budo Village and Darunu Village, Wori District, North Minahasa Regency, it can be concluded that: the total number of seagrass found in the two research locations, namely 6 types of seagrass spread across two research locations, namely there are 4 types of seagrass found in Budo Enhalus acoroiedes Village, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium. Meanwhile, in Darunu Village, there are 6 types of seagrass, namely Enhalus acoroiedes, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium, Halophila ovalis and Halodule pinifoli. Keywords: seagrass, Budo Village, Darunu Village    ABSTRAK Indonesia merupakan negara kepulauan terbesar di dunia yang terdiri dari 16.344 pulau besar dan kecil dengan panjang garis pantai 81.000 km yang kaya akan keanekaragaman hayati memiliki ekosistem laut yang sangat khas seperti terumbu karang, hutan mangrove dan padang lamun. Ekosistem padang lamun di Indonesia biasanya berada diantara ekosistem mangrove dan terumbu karang, atau berada di dekat pantai berpasir dan hutan pantai. Tujuan penelitian untuk mengetahui Perbandingan Jumlah dan jenis Lamun yang terdapat antara desa Budo dan desa Darunu Kecamatan Wori Kabupaten Minahasa Utara. Metode pengumpulan data diawali dengan penentuan lokasi dilakukan dengan melakukan survei langsung dengan menggunakan transek untuk mengetahui kondisi atau keberadaan padang lamun. Transek kuadran terdiri dari frame berbentuk kuadran. Pengambilan data satu transek tiap lokasi, yaitu satu transek di desa Budo dan satu transek di desa Darunu. Dari hasil penelitian di dua lokasi penelitian Desa Budo dan Desa Darunu Kecamatan Wori Kabupaten Minahasa Utara dapat disimpulkan bahwa: jumlah lamun total keseluruhan yang terdapat pada dua lokasi penelitian yakni 6 jenis lamun yang tersebar di dua lokasi penelitian yaitu ada 4 jenis lamun yang terdapat di Desa Budo yaitu Enhalus acoroiedes, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium. Sedangkan di Desa Darunu terdapat 6 jenis lamun adalah yaitu Enhalus acoroiedes, Thalassia hemprichii, Cymodocea rotundata, Syringodium isoetifolium, Halophila ovalis dan Halodule pinifoli.   Kata Kunci: lamun, Desa Budo, Desa Darunu